Estudo sobre a atividade voluntária em crianças pré-escolares à luz da teoria histórico-cultural - Martinati, Adriana Zampieri (2019)
The voluntary activity of children is the focus of this research and it was analyzed from the perspective of children self-motivation in Childhood Education, specifically those acts that suggest that their execution was done in a conscious way to reach a specific goal.The research problem is to answer the question: Is it possible to identify voluntary activity in children of Childhood Education? The main objective of this work is to examine the possibility of developing voluntary activities for children 5 years old. The specific objectives are: (i) to describe and analyze in proposed teaching situations in which voluntary activities of children may occur, (ii) creating experimental conditions for the researcher to identify the possibilities of occurrence of voluntary activity. The method used is based on historical-dialectical materialism and present as study object the voluntary activities in the Municipal School of Childhood Education, located in one city of São Paulo State, and involved 05 years old children, their teachers of childhood education, teachers of arts, the teachers of physical education and also the researcher interventions. The research instruments were used are Political-Pedagogical Project, documentary analysis of participant observation and intervention: narrative interview, toys production, and drawing. The volunteer development process, based on the results obtained from the concrete reality, was manifested through voluntary activity indicators: semantic communicative speech, voluntary choice, choice of materials, activity purpose understatement, interest, formulation of questions, problems resolution/persistence, emotional reactions, interaction/cooperation, creation/imagination, the substitution of objects, imitation, and roles playing. Semantic communicative speech, interaction/ cooperation, and emotional reactions were the most recurrent voluntary activity indicators in participant observation and experimental conditions applied by the researcher. The voluntary choice and materials choice was not very frequent in the activities of Childhood Education and Physical Education, as opposed to Art classes and the researcher interventions. It is possible to note these indicators are intrinsically related to the planning and implementation activities by the teacher, and not to the children development process. The main voluntary activity indicator identified is the understanding of the activity objective (awareness). The collected data indicates children are often aware of the goal of a given activity, they are still guided by impulses external to the activity, which results in non-respect with a rule. Children are in raising awareness of their motivations process and consequently can not control voluntarily their own impulses.The stubbornness and negativism behaviors were observed in relation to the volitional tensions inherent to the activities. In contrast, in the cases where the children spent much of their time sitting around struggling to do the activity, regulation of conduct occurred, perhaps more for fear of threats and possible punishments than for their own conscience. Although the role play appears in the Political-Pedagogical Project of the school as the activity guide in Childhood Education, it was little explored and marked by spontaneity, lack of pedagogical investments and also teacher mediation. In this researched context, the perceived contradictions in the way paper are conceived and worked by teachers for children to reinforce the need for massive investments in initial and continuing teacher education.